Effect of the Nature of Subsequent Environment on Oxytocin and Cortisol Secretion in Maltreated Children - Mizushima, Sakae G.; Fujisawa, Takashi X.; Takiguchi, Shinichiro; Kumazaki, Hirokazu; Tanaka, Shiho; Tomoda, Akemi (Frontiers in Psychiatry, 2015)
Childhood maltreatment (CM), including abuse and neglect is a crucial factor that distorts child development. CM is associated with alterations in numerous brain regions, and may be associated with neuropeptide hormonal dysregulation. This study aimed to investigate differences in secretion patterns of cortisol (CT) and oxytocin (OT) among children who experienced CM, children living in residential care facilities and in unstable environments. Among 38 maltreated children, 23 (mean age = 12.2 years, SD = 3.0) were categorized as “Settled” and 15 (mean age = 13.1 years, SD = 2.2) as “Unsettled”. Twenty-six age- and gender-matched (mean age = 12.6 years, SD = 2.1), typically developing (TD) children were also included. Clinical and psychological assessments, including IQ and trauma evaluations were conducted for all participants. Age, gender and full-scale IQ were used as covariates in hormone analysis. Two saliva samples were collected, one on awakening, the other at bedtime. There were significant differences in the awakening CT levels of the “Unsettled” group, and in bedtime OT levels in the “Settled” group as compared with TD children, and between CM groups. Furthermore, there was a significant difference in trauma-symptomatic depression scores between the “Settled” and “Unsettled” CM group. These results suggest that CT diurnal secretions tend to be reactive to current stress rather previous experience. OT diurnal secretions are presumably hyper-regulated for coping with the environment to survive and thrive. By measuring salivary CT/OT diurnal patterns, hormonal dysregulation of CM children living in “Settled” environments and “Unsettled” environments was indicated.